ASSESSMENT OF CARBON FOOT PRINT OF STUDENS IN CROSS RIVER UNIVERSITY OF TECHNOLOGY, OBUBRA CAMPUS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Natural events are believed to have contributed to an increased global temperature. This is caused primarily by increase in greenhouse gases effect, such as carbon dioxide (CO2). This study evaluated assessment of carbon foot prints in 3 out of the 5 Departments in the Faculty of Agriculture and Forestry, Cross River University of Technology, Obubra Campus. Purposive sampling methods was adopted to involve students studying Animal Science, Agronomy and Forestry base disciplines within the Faculty. Carbon foot print online calculator developed by (WWF, 2016) was used for the assessment. The calculator had well-structured questions to monitor carbon foot print generated by each student activities through food, home, travel and stuff. The results were analyzed using Analysis of Variance (ANOVA). Tables were used to compare with the global average planet of 3.06 tones for human existence on the earth surface. The Department of Animal Science recorded the highest carbon foot print of 614.18 tonnes requiring 6.53 tonnes planets to cohabit. The lowest carbon foot print of 469.0 tonnes was obtained in the Department of Forestry requiring 6.52 tonnes planets to exists. 500 level students generated the highest carbon foot print 356.48 tonnes requiring 7.22 tonnes of global average planets. While, the least foot print was observed in 200 level students 307.54 tonnes. The male and female students produced the same average carbon foot print of 625.3 tonnes. Investigation revealed high carbon foot print in food consumption, travel and home required more planets to sustain our lives in the
Keywords: Carbon, Foot print, University, Obubra